Preparation and antibacterial activity of graphene oxide/cuprous oxide/zinc oxide nanocomposite - Manna Li; Zhaofeng Chen; Yu Sun; Fei Wang; Cao Wu; Jiang Xu; Jianxun Zhang (Materials Research Express, 2021)
In this study, an antibacterial GO/Cu _2 O/ZnO nanocomposite was synthesized by a hydrothermal synthesis method, and its phase and microstructure were characterized by a series of test methods. The results showed that the synthesized cuprous oxide nanoparticals and the added zinc oxide nanoparticals were uniformly dispersed on the surface of graphene oxide, and did not cause the agglomeration of the nanoparticles. The graphene oxide successfully made enhanced the effective surface area of the metal oxide nanoparticles due to its adsorption capacity and chargeability. Thereby enhancing the antibacterial activity of the nanocomposite, reaching a 100% antibacterial rate.